2004
DOI: 10.1021/ja031625a
|View full text |Cite
|
Sign up to set email alerts
|

Helical β-Peptide Inhibitors of the p53-hDM2 Interaction

Abstract: -Peptides differ from R-peptides by one additional backbone carbon atom and by resistance to metabolism and proteolysis. 1a-c -Peptides fold into helices, sheets, and turns and have wellrecognized potential as peptidomimetics. 2 Two -peptides that interact with discrete macromolecular targets are known: a -tetrapeptide hairpin that binds the somatostatin receptor with nanomolar affinity, 1d,e and a highly cationic 3 -decapeptide that binds TAR RNA. 1f Here, we report a set of 3 -peptides that possess signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
267
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(270 citation statements)
references
References 26 publications
2
267
0
1
Order By: Relevance
“…Amongst a multitude of foldamer classes where structural/ conformational determinants have been mapped,1, 2, 3, 4 β‐peptides and hybrid α/β‐peptides, in which β‐amino acids are dispersed along an α‐peptide backbone, can inhibit α‐helix‐mediated protein–protein interactions22, 23, 24, 25, 26, 27, 28, 29 and mimic the structure and the function of protein surfaces 30, 31. Nonetheless foldamers that more accurately mimic the topology and topography of the α‐helix might prove advantageous in comparison to β‐ and α/β‐peptides, which may not fully mimic the spatial presentation of α‐helix side chains.…”
mentioning
confidence: 99%
“…Amongst a multitude of foldamer classes where structural/ conformational determinants have been mapped,1, 2, 3, 4 β‐peptides and hybrid α/β‐peptides, in which β‐amino acids are dispersed along an α‐peptide backbone, can inhibit α‐helix‐mediated protein–protein interactions22, 23, 24, 25, 26, 27, 28, 29 and mimic the structure and the function of protein surfaces 30, 31. Nonetheless foldamers that more accurately mimic the topology and topography of the α‐helix might prove advantageous in comparison to β‐ and α/β‐peptides, which may not fully mimic the spatial presentation of α‐helix side chains.…”
mentioning
confidence: 99%
“…Moreover, the NMR findings support the view that the formation of the large-diameter H18/ 20 P helix is coupled to the head-to-tail association in CD 3 OH. The high-resolution model in Figure 3 reveals that the helix-helix interactions are stabilized by four interchain hydrogen bonds, NH 8 The helical self-association of 4 in CD 3 OH was further investigated by concentration-dependent DOSY NMR spectroscopy. The apparent aggregation number was 3 at a concentration of 100 μm, which rose to 8 at 1 mm (see Figure S6 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Although the formation of secondary structures of peptidic foldamers has been thoroughly studied, their higher-order self-organization (tertiary and quaternary structures) and its effects on the folding propensities are less well understood. It has been shown that peptidic foldamers are able to fold cooperatively into helix bundles; [20] β-and α,β-peptide sequences that were disordered at low concentrations have recently been shown to form quaternary structures through self-assembling helical building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin receptor [7] GLP-1 receptor, [8] PTHR1, [9] the p53-hDM2, [10] the BH3-Bcl-x L [11,12] and the VEGF-VEGFR1 [13] interactions, the gp41 virus cell infusion protein assembly [14], the γ-secretase enzyme [15] and amyloid aggregation. [16] Whilst biomimetic molecular recognition can be achieved with foldamers, their application in therapy, diagnostics and as analytical tools is still a major challenge.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%